Ecogames Playful Perspectives on the Climate Crisis - op de Beke, Laura; Raessens, Joost; Werning, Stefan; Farca, Gerald (Green Media, 2024)
Ecogames, games for change, future worlds, nonhuman epistemologies, metagaming practices